Przestrzenne i instytucjonalne aspekty rozwoju przedsiębiorczości na przykładzie Dolnego Śląska - Adamczuk, Franciszek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The aim of the elaboration is to present spatial and institutional aspects of entrepreneurship's development in Lower Silesia. The author shows spatial aspects of entrepreneurship development. First of all he shows the connection between this aspect with institutional aspect. The main thesis of the research is: Polish Agency of Entrepreneurship Development has the essential significance in the development of entrepreneurship in Lower Silesia. In Wroclaw- the metropolitan kernel and capital of the region - the main role in entrepreneurship's development play business supporting institutions. Such institutions play compatible role in other cities, first of all in Wałbrzych, Legnica, Jelenia Góra and some other towns in the region. Their significance in the entrepreneurship's development is different in comparison with the significance of such institutions localized in Wroclaw. In the end of the elaboration there are evaluations which should be used in the development of the entrepreneurship in Lower Silesia. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (7); 2007; nr 1185, s. 131-142